The Creation Of Rare Musical Instruments | Penciptaan Tabuh Kreasi Karawitan Rare - Pratama, I Gusti Ngurah Juli (GHURNITA: Jurnal Seni Karawitan, 2024)
Childhood is an exciting period to explore; why is that? It is because childhood can determine which direction the child will go. As the creator knows, the term children in Bali is also called Rare. Tabuh Kreasi Rare is a work created due to the creator's anxiety regarding the nature of Rare (children). Rare is a Balinese term for an adult who still has the characteristics of a child. Rare's traits include being easily excited, sometimes crying easily, and getting angry if his desires are not fulfilled. Percussion creation is a Balinese musical composition that has been newly arranged. However, the traditional material elements are still very prominent; what is created are its musical elements, such as content, playing technique, tempo, dynamics, and so on. In the work Tabuh Kreasi Rare, the artist uses the media, said Gamelan Gong Kebyar. Musically, Gamelan Gong Kebyar is a traditional Balinese orchestra with a loud sound ensemble. This percussion work created by Rare uses the Tri Angga structure, which consists of the kawitan, pengawak, and pengecet. In work Tabuh Kreasi Rare, the creator describes three childish traits that will later be analogous to the kawitan, pengawak, and squeak. The kawitan section contains two parts, including flashbacks and joy. The crew part describes the sadness of Rare's character, and in the part of the writer, he makes an analogy about Rare's emotional nature and ending as he grows into an adult.